Hypothalamic Microinflammation: New Paradigm In Obesity And Metabolic Disease - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Indonesian Biomedical Journal, 2020)
BACKGROUND: Hypothalamus is the master regulator of body’s systemic homeostasis including energy balance, body temperature, sleep, blood pressure, and circadian rhythms. This review article will highlight the shifting of the old paradigm of obesityinflammation-metabolic syndrome, which was focused on visceral organs and systemic inflammation, into a new model involving microinflammation in the master regulator of endocrine system, i.e., hypothalamus.CONTENT: Since the early stage of over-nutritional conditions and aging process, microinflammation in hypothalamus has started to emerge, due to the activation of several proinflammatory signaling pathways, especially the nuclear factor kappa B (NF-kB) and c-Jun N-terminal kinase (JNK)-mediated nuclear transcriptional programs. Together with intracellular organelle stress signals, these pathways develop a chronic microinflammatory environment in the hypothalamus leading to obesity and metabolic disorders.SUMMARY: Hypothalamic inflammation has been noted not only as an important driver of impaired energy balance, but also contribute in altered neurocircuit functions and promote obesity-associated metabolic impairment.KEYWORDS: hypothalamus, inflammation, metabolism, obesity, metabolic syndrome